KARAKTERISTIK APENDISITIS PADA PASIEN DI RUMAH SAKIT UMUM HAJI MEDAN PADA JANUARI 2017 - DESEMBER 2019 - AYU ANDIKA BINTANG; ERY SUHAYMI (JURNAL ILMIAH KOHESI, 2021)
Appendicitis is an inflammation of the appendix vermiformis due to infection and bacteria. The main complication inappendicitis is perforation of the appendix. This study aims to determine the characteristics of appendicitis patients at RSUHaji Medan in 2017-2019 based on age, gender, and type of appendicitis. This study was a retrospective descriptive studywith 221 respondents with acute, perforated, and chronic appendicitis patients as seen from the 2017-2019 medical records.Univariate analysis was performed on each research variable and the category of frequency distribution of each variable wasexpressed as a percentage. It was found that there were more women (127 people) with appendicitis than men (94 people).The highest age range was in the 13-19 years age group as many as 73 people (33.0%) and the least in the age group> 70years as many as 1 person (0.5%). Based on the characteristics of the type of appendicitis, it was found that there were 161respondents (72.9%) of the acute appendicitis type, 35 perforated appendicitis (15.8%) and 25 chronic appendicitisrespondents (11.3%). Appendicitis is more common in women aged 13-19 years with acute appendicitis.